(untitled) (Cadernos de Sociomuseologia, 2017)
This article analyses the importance of integration between patrimonialization and Museology for social development. This research was carried out in the city of Salvador, Bahia, Brazil, in the do Abaeté and St. Bartholomew Metropolitan parks. The patrimonialization is analyzed in its sociological and anthropological dimension, considering it as part of the construction of citizenship. The methodological procedures adopted were bibliographical research, archiving, ethnographic observation and interviews. The results showed, on the one hand, an incomplete official patrimonialization, revealing tensions and difficulties in the dialogue between the institutional actors and local communities. On the other hand, patrimonialization although essential, must also respond to the museological demands of the social groups involved with the preserved heritage. There is also a further conclusion about how important it is that coordinated policies be formulated so as to make viable the integration patimonialization and museology as a means of stimulating local development. Keywords: patrimonialization, museology, public policies, developme